THE IMPACT OF IMPLEMENTING THE DIGITAL TECHNOLOGY INNOVATION ON BANKING PERFORMANCE IN INDONESIA - Dharsono, Selvi; Arifin, Agus Zainul (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to obtain empirical evidence whether customer experience and customer satisfaction affect the financial performance of a bank for users digital banking in Indonesia. The number of samples in this study were 261 respondents. The criteria for respondents in this study are respondents who live in Jakarta, Bogor, Depok, Tangerang and Bekasi and respondents who are users of banking services digital banking. This study uses a non-probability sampling technique. Data collection techniques through questionnaires online. Data analysis using PLS-SEM. The result of the first research is that customer experience has a positive effect on financial performance. Second, customer satisfaction has a positive effect on financial performance.